1976
DOI: 10.1152/ajplegacy.1976.230.3.777
|View full text |Cite
|
Sign up to set email alerts
|

Increase in renin release after sionaortic denervation and cervical vagotomy

Abstract: The role of the vagi in the control of renin secretion was investigated in dogs maintained on a high-salt diet. Renal perfusion pressure was maintained relatively constant by the manipulation of a suprarenal aortic snare. Mean arterial blood pressure (MAP), plasma renin activity (PRA), and packed cell volume (PCV) increased after sinoaortic denervation and cervical vagotomy. Cooling of cervical vagi to 3-5 degrees C had the same effect as vagotomy. There was no change in MAP, PRA, and PCV in sham-operated anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…In dogs maintained on a high-salt diet sinoaortic denervation caused increases in mean arterial pressure (MAP), PRA, and PCV, and cervical vagotomy caused further increases in these variables. This confirms an earlier report (2). Figure In the animals whose kidneys had been denervated 7-1 0 days previously, sinoaortic denervation caused increases in mean MAP from 133.1 +_ 5.4 mm Hg during control periods to 181.9 2 8.0 mm Hg ( P < 0.005) 60 min after sinoaortic denervation; it increased further to reach 21 1.…”
Section: Materials and Methods ( A ) General Surgical Proceduressupporting
confidence: 89%
See 4 more Smart Citations
“…In dogs maintained on a high-salt diet sinoaortic denervation caused increases in mean arterial pressure (MAP), PRA, and PCV, and cervical vagotomy caused further increases in these variables. This confirms an earlier report (2). Figure In the animals whose kidneys had been denervated 7-1 0 days previously, sinoaortic denervation caused increases in mean MAP from 133.1 +_ 5.4 mm Hg during control periods to 181.9 2 8.0 mm Hg ( P < 0.005) 60 min after sinoaortic denervation; it increased further to reach 21 1.…”
Section: Materials and Methods ( A ) General Surgical Proceduressupporting
confidence: 89%
“…Mancia et al (5) have shown in the dog and Clement et al (8) in the rabbit that cervical vagotomy causes an increase in sympathetic discharge to the renal nerves. We also showed in our earlier report that infusion of propranolol abolishes the increase in PRA that follows cervical vagotomy (2). In the present series of experiments, we show as well that in dogs whose kidneys have been denervated for 7 to 10 days, cervical vagotomy causes only a slight, but not statistically significant, increase in PRA (Fig.…”
Section: Materials and Methods ( A ) General Surgical Proceduressupporting
confidence: 88%
See 3 more Smart Citations